Tracing young SMBHs in the dusty distant universe – a Chandra view of DOGs. Issue Volume 15:Issue S359(2020) (March 2019) - Menéndez-Delmestre, Karín; Riguccini, Laurie; Treister, Ezequiel
Abstract: The coexistence of star formation and AGN activity has geared much attention to dusty galaxies at high redshifts, in the interest of understanding the origin of the Magorrian relation observed locally, where the mass of the stellar bulk in a galaxy appears to be tied to the mass of the underlying supermassive black hole. We exploit the combined use of far-infrared (IR) Herschel data and deep Chandra ˜160 ksec depth X-ray imaging of the COSMOS field to probe for AGN signatures in a large sample of >100 Dust-Obscured Galaxies (DOGs). Only a handful (˜20%) present individual X-ray detections pointing to the presence of significant AGN activity, while X-ray stacking analysis on the X-ray undetected DOGs points to a mix between AGN activity and star formation. Together, they are typically found on the main sequence of star-forming galaxies or below it, suggesting that they are either still undergoing significant build up of the stellar bulk or have started quenching. We find only ˜30% (6) Compton-thick AGN candidates (N H > 10 24 cm –2 ), which is the same frequency found within other soft- and hard-X-ray selected AGN populations. This suggests that the large column densities responsible for the obscuration in Compton-thick AGNs must be nuclear and have little to do with the dust obscuration of the host galaxy. We find that DOGs identified to have an AGN share similar near-IR and mid-to-far-IR colors, independently of whether they are individually detected or not in the X-ray. The main difference between the X-ray detected and the X-ray undetected populations appears to be in their redshift distributions, with the X-ray undetected ones being typically found at larger distances. This strongly underlines the critical need for multiwavelength studies in order to obtain a more complete census of the obscured AGN population out to higher redshifts. For more details, we refer the reader to Riguccini et al. (2019 ).